Addressing challenges in providing a reliable ecotoxicology data for graphene-oxide (GO) using an algae (Raphidocelis subcapitata), and the trophic transfer consequence of GO-algae aggregates. (April 2020) - Markovic, Marijana; Andelkovic, Ivan; Shuster, Jeremiah; Janik, Leslie; Kumar, Anupama; Losic, Dusan; McLaughlin, Michael J.
Abstract: The graphene oxide (GO) due to its exceptional structure, physicochemical and mechanical properties is a very attractive material for industry application. Even though, the unique properties of GO (e.g. structure, size, shape, etc.) make the risk assessment of this nanomaterial very challenging in comparison with conventional ecotoxicology studies required by regulators. Thus, there is a need for standardized characterization techniques and methodology to secure a high quality/reliable data on the ecotoxicology of GO, and to establish environmentally acceptable levels. Herein, authors address the crucial quality criteria when evaluating the ecotoxicology of GO using an algae ( Raphidocelis subcapitata ) and a shrimp ( Paratya australiensis ). This study provides a detail characterization and modification of the used GO, robust quantification and a suspension stability in different media for ecotoxicology studies. It was observed that under the same exposure conditions the behavior of GO and the estimated outcomes (IC50 values) in modified algae media differed in comparison to the referent media. Further to that, the adverse effects of GO on the algae cell structure and the potential uptake of GO by the algae cells were examined using the TEM with different staining techniques to avoid artefacts. Shrimps which were exposed to GO-algae aggregates via the food intake did not indicate stress or accumulation of GO. Our work presents an important insight to necessity of establishing a benchmark ecotoxicology assays for GO (e.g. characterization techniques, choice of media, etc.) and providing a reliable data to be used by regulators in risk assessment of two-dimensional (2D) nanomaterials. Highlights: Ecotoxicology of modified graphene-oxide (GO) was assessed using an algae. The adverse effects of GO-algae aggregates were estimated using a shrimp. Characterization, quantification and suspension stability of GO were addressed. Specific surface area and the shape of GO were affected by the composition of media. Osmium helped to avoid bias and gave a reasonably good images of algae sections.